MAKNA ETIS “PUNJUNG NASI SAWO” PADA ACARA PERNIKAHAN SUKU REJANG DI KECAMATAN BATIKNAU KABUPATEN BENGKULU UTARA - Irsal Irsal (Sekolah Pasca Sarjana IAIN Bengkulu, 2017)
Abstract: This research was motivated by the reality on the ground that there was a traditional ceremony in Rejang tribe “Punjung Nasi Sawo”. The Rsearcher assumed that this tradition had a religious or moral message. The formulation of the problem in this study was what the symbolic meaning contained from the “Punjung Nasi Sawo” at the wedding of Rejang tribe in Batiknau district of North Bengkulu, what the ethical was contained in the procession of Punjung Nasi Sawo at the wedding of Rejang tribe in Batiknau district of North Bengkulu and how the manufacturing process and materials used in presenting the “Punjung Nasi Sawo”. This research had the goal was to determined and analyzed the symbolic meaning contained from the “Punjung Nasi Sawo” at the wedding of Rejang tribe in Batiknau district of North Bengkulu, to analyze the meaning of ethical contained in procession of “Punjung Nasi Sawo” at the wedding of Rejang tribe in Batiknau district of North Bengkulu and to determine and analyze the manufacturing process and materials used in the presentation of the “Punjung Nasi Sawo”?. To obtained information on the ground, the researcher used a type of field research with a qualitative approach. Based on the results of the study “Punjung Nasi Sawo” on the Marriage Event of Rejang tribe in Batiknau district of North Bengkulu revealed that the activity was performed at the time of Raja Penghulu Consensus (madeak kutai), the event was attended by community leaders that consists of traditional leaders, religious leaders, government of the village and the general public. The activity of Raja Penghulu Consensus (madeak kutai) included several items of rejang tribe, one of them was “Punjung Nasi Sawo” and the event was held in the outdoors (taruf). Besides, these activities showed that the implementation of the Raja Penghulu Consensus (madeak kutai) which included one of rejang tribe “Punjung Nasi Sawo” that had some moral values, ethical, social, anthropology and religion. In addition, Punjung Nasi Sawo symbolized as a noble hope against both the bride and groom, as a form of guarantee, as a form of application for license to community leaders, religious leaders and the surrounding communities and to establish with nurture event Silahturahim rope. This is in accordance with the customary slogan of Rejang tribe “ adat bersendikan syara’’, syara’ bersendikan kitab Allah. It means that the culture remains preserved all relied on the law and the provisions of Islamic Sharia.